Bachelor of Applied Sciences (Hon.) Material Technology - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Chin, Mei Lee; Siti Aisah, Harun; Norhayati, Nordin; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras; Nurul Nadia, Abd Razak (Penerbit UMP, 2011)
Universiti Malaysia Pahang is committed to developing new and innovative programs to ensure our graduates are equipped wfth the skills and knowledge relevant to today's market demands. The Faculty of Indust rial Sciences & Technology (FIST) will be offering the new MQA-accreditated Bachelor of Applied Sciences (Hon.) Material Technology.